Lensbaby : bending your perspective - Hilz, Corey (Focal Press, 2013)
"If you've ever wished you could learn about all of the creative possibilities the Lensbaby offers, this is the book for you! Seeing subjects with a new perspective is at the heart of the Lensbaby experience, and with the essential information found in this book, you'll be able to take your creative exploration to the next level. Written by Lensbaby Guru Corey Hilz, Lensbaby: Bending Your Perspective starts off with an overview of each lens in the Lensbaby suite. Then comes the fun stuff! Packed with tips on composition and techniques for capturing your best images, you'll be immersed in the wonderful world of Lensbaby in no time. On nearly every page you'll find a full color image created by a Lensbaby expert to inspire your own shooting. You'll also find complete coverage of all of the Lensbaby accessories, from the Optic Swap System to a macro kit, creative aperture discs, and a super wide angle lens. With this gorgeous and practical book by your side, you'll never see the world in the same way again."--Provided by publisher